Electrostatic and Non‐covalent Interactions in Dicationic Imidazolium–Sulfonium Salts with Mixed Anions. Issue 15 (3rd March 2014) - Fei, Zhaofu; Zhu, Dun‐Ru; Yan, Ning; Scopelliti, Rosario; Katsuba, Sergey A.; Laurenczy, Gabor; Chisholm, Danielle M.; McIndoe, J. Scott; Seddon, Kenneth R.; Dyson, Paul J.
Abstract A series of thioether‐functionalised imidazolium salts have been prepared and characterized. Subsequent reaction of the thioether‐functionalised imidazolium salts with iodomethane affords imidazolium–sulfonium salts composed of doubly charged cations and two different anions. Imidazolium–sulfonium salts containing a single anion type are obtained either by a solvent extraction method or by anion exchange. The imidazolium–sulfonium salts undergo a methyl‐transfer reaction on exposure to water, giving rise to a new, singly charged imidazolium salt with iodide introduced at the 2‐position of the imidazolium ring. Crystal structures of some of the imidazolium–sulfonium salts were determined by X‐ray crystallography providing the topology of the interactions between the dications and the anions. Electrospray ionization mass spectrometry and quantum‐chemical calculations were used to rationalise the relative strength of these interactions.